Jirqa Learning Strategies: Influence Student Learning Outcomes Based on Motivation Level - Faizatuluhmi, Silfi; Komala, Ratna; Rusdi, Rusdi (International Journal for Educational and Vocational Studies, 2020)
The current learning process emphasizes the development of student skills as life skills, one of the goals is effective communication skills that are helped through knowledge from reading results. A syntactic integration between Jigsaw learning strategies and Reading, Questioning, Answering or called JiRQA learning strategies based on motivation level of student learning outcomes can help students to face the demands of the 21st century. This study aims to measure the effect of using JiRQA learning strategies based on motivation level of student learning outcomes. The research method is quasi-experimental. Data analysis was performed in the normality test using the Kolmogorov-Smirnov test, while the homogeneity test was carried out with the Bartlett test then for the hypothesis test carried out with a 2 x 2 factorial experimental design. The sample size was 18 experimental class students and 18 control class students in SMAN 11 Pandeglang. The results of the study showed normal and homogeneous (p> 0.05). The results of the study using two-ways ANAVA test obtained data that the value of p = 0.014, which means p <0.05 (starting Ho). And make conclusions there is an interaction between JiRQA learning strategies based on the level of motivation on learning outcomes. Similar research needs to be done to get more information. The research findings are the influence of syntactic integration between Jigsaw and Reading, Questioning, Answering learning strategies on learning results based on motivation level.